(untitled) (Revista Venezolana de Salud Pública, 2021)
COPD and cardiovascular diseases represent the most important causes of morbidity and mortality in the elderly. The aim of this study was to describe cardiac function through two-dimensional transthoracic echocardiography in a group of Venezuelans COPD patients. Average age of patients was 66.7 ± 0.9 years; 60.7% were male and 82% were smokers. Group B male patients showed larger mass, left ventricle final systolic volume and E/Em ratio in comparison to patients from other groups although all values were normal; 92% had normal systolic function and 40.7% had diastolic dysfunction. Female patients from groups B and D showed larger mass and left ventricle final systolic volume; 97% had normal systolic function and 45.7% had diastolic dysfunction. In general, patients from B and D groups showed a tricuspid E/A value suggestive of right ventricle relaxation impairment. COPD affects predominantly mass and left ventricle final systolic volume as well as relaxation of the right ventricle in patients from group B. In COPD patients with relatively stable lung function but with persistent respiratory symptoms, prompt cardiovascular evaluation could detect pathologies that may impact this group morbidity and mortality.